Innovation of Financial Accounting Practices through the Design of SAK-Based Financial Accounting Applications - Raya Puspita Sari Hasibuan; Cut Nizma; Anita Putri; Rahmadani Rahmadani (Journal of Social Research, 2024)
Applied Innovation Research (PTI) aims to create a SAK-based financial application design for MSMEs and SMEs in financial management and production activities. The design will be applied in student practicum for financial accounting courses at Medan State Polytechnic, a Vocational State University. The goal is to create a simple design for financial accounting applications that will be used by MSMEs and classroom learning activities. The main goal is to develop students and MSMEs' technology skills, even if they lack good abilities. The PTI project partners with other universities with IT-capable human resources to collaborate on utilizing existing competencies in accounting and Information Technology science. The goal is to create a digitalized, accessible, and user-friendly financial accounting application that will benefit both students and SMEs.